Microbes and microbial technology agricultural and environmental applications - Ahmad, Iqbal; Ahmed, Farah; Pichtel, John 1957- (Springer New York, 2011)
Awareness of the role of microbes and microbial biotechnology in improving the quality of life has been recognized worldwide. Today, what is needed is an exploration of new microbes and novel genes for solving some of the major challenges of the 21st century with particular reference to sustainable agriculture, the environment and human health. This book addresses applied microbiology and microbial technology, and serves as an overview of recent advances in the field. It includes microbial diversity exploration and detection of microbial pathogens in food, concepts and applications of microbial biofilms, genetic exchange in bacterial populations in the natural environment, classical and modern techniques for studying and tracking plant growth-promoting rhizobacteria, bioremediation of contaminated soil and water using microbial surfactants, bioaugmentation-assisted phytoremediation, and degradation of agricultural pesticides by soil bacteria. Biosorption of common heavy metals by microbial biomass, recent trends in the role of baculoviruses and fungal-based agents in controlling plant pests and disease, and production technology of mycorrhizal fungi are addressed in depth. Trends in new frontiers of microbiology such as quorum sensing, biosensors, nanobiotechnology and probiotics are also covered.